Dukungan Keluarga sebagai Stimulus Kepatuhan Minum Obat ARV penderita HIV - Bangun Dwi Hardika (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Human Immunodeficiency Virus (HIV) is a virus that attacks the human immune system, where the population increases every year around the world. Therapy to help inhibit the development of the virus in HIV sufferers is antiretroviral drugs (ARVs). This ARV consumption will be carried out in the long term, even throughout his life. So it is necessary to have HIV patient compliance in taking ARVs. One source of stimulus for adherence in taking medication is family support so that the quality of life of HIV sufferers is better. The purpose of this study was to find out whether the family is a source of support for HIV sufferers for adherence to taking ARV medication. This research is a type of quantitative research that uses an analytic survey method with a cross-sectional research design with a total of 32 respondents living with HIV and the results of the study were analyzed using the Kendall Tau statistical test. The results of the study from 32 respondents, there were 16 people (50.0%) with a high category of family support. The results of Kendall Tau's statistical test analysis found that there was no significant relationship between family support and adherence to taking ARV medication with a p-value = 0.347. It is hoped that people with HIV can increase their adherence to taking ARV drugs and be more open to their families so they can receive other forms of support from their families.